2017
DOI: 10.17219/pim/68646
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Knee Joint Stability Following Anterior Cruciate Ligament Reconstruction Using the Ligament Advanced Reinforcement System

Abstract: The anterior cruciate ligament (ACL) of the knee joint plays a complex role in the stabilization of the knee joint, resisting anterior displacement and excessive rotation of the tibia relative to the femur [1]. Reconstruction of the ACL of the knee joint [2] followed by a postoperative physiotherapeutic procedure [3] is the standard ACL injury treatment for individuals wishing to return to high-level sports activities. There are numerous current treatment options for ACL reconstruction, and in choosing the tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
(39 reference statements)
0
6
0
1
Order By: Relevance
“…Krupa et al . also indicated a significant progress from preoperative to short‐term postoperative result in reducing anterior translation and anterolateral rotational instability of the tibia relative to the femur in patients who had undergone ACL reconstruction with a synthetic LARS graft.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Krupa et al . also indicated a significant progress from preoperative to short‐term postoperative result in reducing anterior translation and anterolateral rotational instability of the tibia relative to the femur in patients who had undergone ACL reconstruction with a synthetic LARS graft.…”
Section: Discussionmentioning
confidence: 95%
“…Regardless of its type, autograft harvest can result in a degree of morbidity, which may negatively affect recovery after ACL reconstruction. The use of allografts has increased in recent years because they offer less donor‐site morbidity, shorter surgical and anesthesia times, fewer postoperative complications, faster postoperative recovery, lower incidence of postoperative arthrofibrosis, less postoperative pain, and an unlimited graft source in the setting of multi‐ligament and revision reconstructions. However, allografts are associated with a higher expense, a risk of disease transmission, delayed healing, ligamentization, and an increased risk of graft rupture in the younger, more active population.…”
Section: Introductionmentioning
confidence: 99%
“…The short-term postoperative results of patients after ACL reconstruction with the use of LARS are very satisfying. 48 A mean 2.5-year follow up carried out by Dericks in 1995 revealed encouraging results of treatment with the use of LARS. 47 Also, a follow-up at a mean of 8 years reported by Parchi et al in 2013 showed satisfying results reflected in no postoperative complication occurrence and only one case of LARS rupture.…”
Section: Ligament Advanced Reinforcement System (Lars)mentioning
confidence: 98%
“…Нативна ПСЗ 2160±157 242±28 [45] BPBT 10 мм 2238±316 455±67 [47] QTB 10 мм 2353±495 621±122 [48] 4-пучковий сухожилок тонкого та напівсухожилкового м'яза 4090±295 276±204 [46] 2-пучковий сухожилок тонкого м'яза 1550±369 370±108 [46] 2-пучковий сухожилок напівсухожилкового м'яза 2640±320 534±76 [46] новлення у післяопераційний період, необмеженість у кількості та виборі типу і розміру трансплантату [63,64] Summary. Of all knee injuries, the most common one is the anterior cruciate ligament (ACL) injury.…”
Section: джерело літературиunclassified